INTELLIGENT INFORMATION E-COMMERCE SYSTEM FOR CLOTHING BRAND - KONDRA, ARTUR; KUNANETS, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The relevance of the program is to implement the client part with a chatbot, which makes the interface simple for the client and helps the administrator to obtain detailed statistics of client actions for further analysis. The intelligent e-commerce information system of the clothing brand uses a database and filters information that meets the user’s request. The task of the project is to develop a software product that implements an algorithm that will allow you to select products and add them to the shopping cart. The software product consists of a chatbot and a web application. The chatbot is designed for customers and helps to view available products, select the required number of products and add these products to the cart, also provides an opportunity to view a list of all products in the cart. The web application is designed for the administrator, and allows you to edit content, track customer activity and view the shopping cart. During the completion of this thesis, development and research were conducted, as well as the implementation of a chatbot and a web application that provides information support in e-commerce of the clothing brand. The theoretical concepts of intelligent information system and e-commerce in general are studied and certain aspects that are essential for the topic of qualification work are described in more detail. Information on the basic parameters of the intelligent information system of e-commerce of the clothing brand is given, the analysis of classification and features of analogues is carried out. A comparative analysis of all existing software options to solve the problem and selected the most effective. The implementation of the information system used a functional approach in combination with object-oriented. JavaScript programming language and a number of closely related frameworks have been chosen for development. As a result of the last section, an intelligent information system for e-commerce of the clothing brand was created. The designed structure of the program, database was analyzed and the server part of the system was created. The main functions of the future system, the sequence of processes and the relationships between them are identified. Also analyzed and selected system and software tools needed to implement the tasks. A ready-to-use software product was developed.